PENGARUH UKURAN PERUSAHAAN, FINANCIAL DISTRESS, DAN REPUTASI KAP TERHADAP AUDIT REPORT LAG - Laudza Indra Perdana; Herry Laksito (Diponegoro Journal of Accounting, 2023)
This research was conducted with the aim of examining the effect of firm size, financial distress, and KAP reputation against audit report lag. The variable used in this study are firm size, financial distress, KAP reputation as an independent variable as well as the dependent variable used is audit report lag.The sample chosen in this study is a registered service sector company listing on IDX in 2020-2021 with a total sample of 520 samples. Selection of the sample to be used using purposive sampling approach with the criteria and requirement determined by the researcher. The hypothesis analysis used by researchers in testing the hypothesis is multiple linier regression analysis.The result of the study found that all variables, firm size, financial distress, and KAP reputation simultaneously affect the dependent variable audit report lag. When review partially, the variables firm size, financial distress and KAP reputation simultaneously have a negative and significant effect on variables audit report lag.